China and India in world trade: Are the Asia giants a threat to Malaysia? - Devadason, E.S. (2008)
With higher shares in world merchandise trade and improvements in product quality, China is better positioned than India in the near term for influencing global trade. From the Malaysian perspective, China represents a non-negligible share in Malaysia's trade. The trends in bilateral trade with both Giants suggest that competition has intensified. Relative to India, China appears to promulgate a more influential role on Malaysia via higher commodity market overlap in external markets, greater matched trade that is of vertical differentiation, distinct quality shifts and negative adjustment pressures. Within this broad rubric of trade-induced changes, there is no evidence of skill upgrading for Malaysia in trade expansion with both Giants. This mirrors the lack of product quality improvement and the low levels of export values of high quality varieties in matched trade. Hence trade induced changes from the Giants that have been cited to be favourable from the Malaysian perspective in previous studies, may have been grossly overstated.